Like China, the Chinese banking sector is in a class of its own - Zuzana Fungáčová; Iikka Korhonen (Bank of Finland, Institute for Economies in Transition (BOFIT), 2011)
This paper provides an overview of the Chinese banking sector, which has expanded tremendously over the past two decades. We first describe aggregate developments of the sector and compare them to the situation in other countries. Also, various financial institutions that operate in China are analyzed. Our results confirm that the Chinese banking sector is truly in a class of its own, especially given the level of China's economic development. Despite significant reforms, the state and various public organizations still own controlling shares in the largest commercial banks. The state is also present on the borrowers' side; it is estimated that about half of state-owned commercial bank lending still goes to state-controlled companies. In this way, the banking system can serve as an important policy tool. Another distinctive feature of the Chinese banking sector is the variety of its banking institutions. New types of banking institutions, especially those serving rural areas, are emerging all the time. While equity and debt markets are still tiny relative to the banking sector and their importance as sources of financing of investment remain minor, they have evolved rapidly in recent years.
URN:NBN:fi:bof-201408072098
Keywords: G28; P34; G21; 330; China; banking sector; state banks